Rehabilitation Protocols after Shoulder Capsuloplasty: A Literature Review - Valência, Michelle Rosana Paniça (2010)
The main goal of this study was to perform a literature review on the various protocols for post-surgical rehabilitation of patients who underwent capsuloplasty. The study was done through online electronic search in databases focusing scientific articles from 1997 to 2008, besides search in specialized journals and textbooks at Cesumar Library. The glenohumeral instability can be classified as front, rear and multidirectional according to the directions and can also be classified concerning its etiology into traumatic and non-traumatic, being possible to initially apply the conservative treatment. The cases that do not respond to the conservative rehabilitation can be treated surgically using methods that reduce the capsular volume and cause an increase in capsule resistance. Regardless the surgical technique used in order to achieve success in post-surgical rehabilitation, it is necessary a perfect understanding between the surgeon and the physiotherapist, who should immediately proceed to the rehabilitation process, in addition to providing information to patients about the prognosis and time of rehabilitation. A well planned and comprehensive rehabilitation program, that allows range of motion, flexibility, coordination and muscle strength rehabilitation must be valued before returning to sports or heavy lifting.